2019
DOI: 10.1007/s11357-019-00131-w
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of necroptosis in inflammaging and aging

Abstract: An age-associated increase in chronic, lowgrade sterile inflammation termed "inflammaging" is a characteristic feature of mammalian aging that shows a strong association with occurrence of various ageassociated diseases. However, the mechanism(s) responsible for inflammaging and its causal role in aging and age-related diseases are not well understood. Ageassociated accumulation of damage-associated molecular patterns (DAMPs) is an important trigger in inflammation and has been proposed as a potential driver o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 151 publications
2
87
0
1
Order By: Relevance
“…All of the current HCC mouse models exhibit HCC in relatively young adult mice. The Sod1KO mice, which show an accelerated aging phenotype (28), develop HCC in the later third of their life, similar to what is seen in humans. Because a variety of factors change with age that can impact cancer, the Sod1KO mice allows one to study HCC in the environment of an aged animal that is relevant to HCC in humans.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…All of the current HCC mouse models exhibit HCC in relatively young adult mice. The Sod1KO mice, which show an accelerated aging phenotype (28), develop HCC in the later third of their life, similar to what is seen in humans. Because a variety of factors change with age that can impact cancer, the Sod1KO mice allows one to study HCC in the environment of an aged animal that is relevant to HCC in humans.…”
Section: Introductionsupporting
confidence: 59%
“…Studies have shown that necroptosis is a major source of inflammation in a variety of tissues, and genetic or pharmacological inhibition of necroptosis can block/reduce inflammation (28). In addition, necroptosis has been reported to be elevated in the livers of patients with CLD (16,17) and also in the livers of mouse models of diet-induced NAFLD (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanically, upon pathogenic stimuli following TBI, TNF-α-induced receptor-interacting protein 1 activation contributes to the formation of the so-called necrosome, a complex necessary for necroptosis [40,41]. And after necroptosis, inflammatory factors released from damaged cells flow into the extracellular space, boosting the neuroinflammation [41][42][43]. All these primary or secondary pathologic mechanisms contribute to cell death, tissue loss, structural and metabolic abnormalities, and an ultimate neurological dysfunction in the patients [15,44].…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells are important constituents of the TME and participate in tumour immune escape and tolerance [54,55]. A large number of studies have shown that there are signi cant differences in the in ltration ratio of immune cells between colon cancer tumour tissues and corresponding adjacent tissues, and is characterised by extensive heterogeneity.…”
Section: Discussionmentioning
confidence: 99%